Insight into IELTS : the Cambridge IELTS course - Jakeman, Vanessa. (Cambridge University Press, 1999)
This book consists of four parts: Listening, Reading, Writing and Speaking sections; Supplementary activities for each unit; A complete practice test; and Recording Script and Answer Key.